#TITLE_ALTERNATIVE# - Dwi Astuti ( NIM : 15113022), Nita
Indonesia lies on four major active plates, Eurasia, Indo-Australia, Pacific, and Philippine Sea Plate (Bock et al, 2003). Thus, Indonesia has a lot of active volcanoes, included Gede Volcano which located in Sukabumi and Bogor Regency, West Java. This volcano has 2958 meters height above sea level. Gede volcano history eruptions had been studied by Junghun (1843) and Traverne (1926) in Kusumadinata K and Hamidi S (1979), explained that Gede volcano eruptions generally insignificant and short in time. One method of monitoring the volcanic activity is the deformation method. In conducting the study of deformation that occurs, the data of observational GPS survey is used. Basically, this survey was conducted to find out the pattern and rate of deformation which occurs in Gede volcano. From an analysis of the elements of this deformation, the deformation characteristics of the volcano can be found. This research focuses on the determination of horizontal displacement and strain from the station CORS in Gede volcano in 2014 up to 2017. The point used are CLDO, MKRJ, MKRW, PUTR, and PSBL. Data processing using scientific software GAMIT/GLOBK 10.6. Based on the GPS data observation, displacement magnitude of GPS observation points at Gede volcano from 2014Ã‚Â–2017 is ranging from -13.7900 Ã‚Â± 0.190 to 8.0758 Ã‚Â± 0.130 mm in east component and -19.793 Ã‚Â± 0.164 mm to 19.897 Ã‚Â± 0.166 mm in the north component. The results of strain are ranging from 0.235 to 5.868 μstrain for extension and -0.022 to -5.125 μstrain for shortening component. The area strain shows that the Gede volcano dominated by extention and baselines of observation dominated with lengthen. The displacement occurred due to the local volcanic earthquake as a result of increased activity of Gunung Gede, especially at the end of 2015 and 2016. The displacement pattern and area strain show that direction of volcano movement is southwest from crater.